PARENTAL ALCHEMY: NURSE -LED INTERVENTIONS IN TRANSFORMING BEHAVIOURAL CHALLENGES - Gayathri Kannadasan,; Shankar Shanmugam Rajendran,; Kannan Kasinathan,; Grace Anita Samuel,; Savinitha Jose,; Uma Rajaraam Sarasu,; Winston Thomas Sundarsingh, (The Bioscan, 2025)
Behavioural problems in children refer to persistent patterns of disruptive, aggressive, defiant, or socially inappropriate behaviours that are not appropriate for the child’s age and developmental level. These behaviours often interfere with the child’s learning, social interactions, and daily functioning at home, school, or in the community. Mothers of children with behavioural problems often struggle with parenting and frequently adopt arbitrary or inconsistent approaches. In this study, non-probability convenience sampling was used to select eight mothers of children with behavioural problems for the phenomenological qualitative phase, and stratified purposive sampling was employed to select 60 mothers for the pre-experimental study design. Data were collected through semi-structured interviews for the qualitative phase, and the Parenting Practices Scale was used in the pre-experimental phase to assess parenting styles. The study explored and revealed six major themes: instruction, struggle, support, financial support, knowledge, and parenting burden. Each theme included specific sub-themes. The theme of instruction comprised admonition, parental presence, and non-compliance. Under the theme of struggle, the sub-themes of exasperation and altruism were identified. The support theme included husband and family support. The financial support theme encompassed schooling expenses and financial burden. The parenting burden theme consisted of sub-themes such as educational responsibilities, nurturing, guilt over ineffective parenting, and the emotional and mental well-being of mothers. This study highlighted the profound parenting challenges faced by mothers of children with behavioural problems. The insights gained from the semi-structured interviews were used to develop an appropriate intervention. Following the qualitative phase, the parenting styles of the mothers were evaluated using the Parenting Practices Scale, and the intervention was implemented effectively, as evidenced by the positive post-intervention results.